Culinary Product Transformation: Training and Innovation in Making Chicken Bengkuang Spring Rolls - Handayani, Dewi; Riyanti, Rossa; Mestiragita, Yeptin Pra; Zakiah, Zabrina Wardah Annafsatuz (Salus Publica: Journal of Community Service, 2025)
Indonesia has a wealth of traditional culinary delights with potential for further development. This activity aims to create innovative spring rolls with chicken and jicama and provide skills training to boost interest in culinary entrepreneurship. The activity consisted of socialization, demonstrations, and hands-on guidance on making the spring rolls for six participants. The results show the training effectively improved manufacturing skills and sparked interest in innovative lumpia-based businesses. This program could serve as a model for adapting traditional cuisine to market trends while strengthening the creative economy based on local culture. The distribution of participant response questionnaires yielded the following results: 90% stated that the training material was relevant to industry/entrepreneurship needs. The instructor's delivery method (practice) was easy to understand (85%). The training duration was sufficient to master core skills (80%). The tools and materials provided were sufficient to facilitate the training activities (80%), and an open suggestion was for further training related to product labeling and marketing.